2013
DOI: 10.1108/k-03-2013-0060
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of cash flow forecasting

Abstract: Purpose -The aim of this study is to show in detail the theoretical and practical foundations of a new feasibility technique for cash flow forecasting (CFF) based on triangular fuzzy numbers. Design/methodology/approach -One of the most complicated problems business people face is determining if they have enough cash to be able to meet all future payments of a specific period. The uncertainty of forecasting the data to solve the problem suggests that a model based on fuzzy logic tools may provide a good way to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…It is also possible that we ourselves have to own the correct distributions, as the selected spreadsheet has no built-in tool for that move. For example, Linares-Mustarós et al (2013) suggested using fuzzy logic, which is not available directly in most programmes, for estimating corporate liquidity problems. They point out: this approach provides a practical estimate of the frequency of payment difficulties and, with some learning, this approach can be easily adapted to the models of spreadsheet programmes widely used in corporate environment, as well.…”
Section: Monte Carlo Simulationmentioning
confidence: 99%
“…It is also possible that we ourselves have to own the correct distributions, as the selected spreadsheet has no built-in tool for that move. For example, Linares-Mustarós et al (2013) suggested using fuzzy logic, which is not available directly in most programmes, for estimating corporate liquidity problems. They point out: this approach provides a practical estimate of the frequency of payment difficulties and, with some learning, this approach can be easily adapted to the models of spreadsheet programmes widely used in corporate environment, as well.…”
Section: Monte Carlo Simulationmentioning
confidence: 99%
“…The fact that the figure contains gray indicates that this subset cannot be considered as a classic subset of the reference set, since there could only be black and white colors, symbolizing that either the object meets a certain property or does not meet it. The acceptance of the fundamentals of the fuzzy subset theory allows us to find better solutions to general problems more simply for the same type of modeling (Linares-Mustarós, Ferrer-Comalat & Cassú-Serra, 2013;Linares-Mustarós, Merigó & Ferrer-Comalat, 2015;Linares Mustarós, Ferrer Comalat, Corominas Coll & ---Merigó,2019;Ferrer-Comalat, Linares-Mustarós & Corominas-Coll, 2016, 2018Corominas, Ferrer-Comalat, Linares-Mustarós & Bertran, 2017), and to create new techniques that are currently used in various industrial applications, such as control systems used to focus video cameras or for vehicle brakes (Terán et al, 1987;Kaufmann & Gupta, 1988).…”
Section: Fuzzy Subset Theorymentioning
confidence: 99%
“…First, given the complexity of reality, a decision must always be made regarding the choice of variables, either by reasoning why they are considered essential to the model [2,3] or through statistical studies, using a data set to look for variables that can be deleted [4]. Second, there is the decision of what kind of relationship the model should represent between the variables [5][6][7]. The choice of relationships is made while waiting for the model to be able to predict behaviors or quantify aspects of the system in question.…”
Section: Introductionmentioning
confidence: 99%